Analisis Dampak Covid-19 Terhadap Akses Rumah Tangga Atas Pelayanan Dasar Dengan Metode Klaster - Ananda Putri Mitra; Sazia Husna (Seminar Nasional Official Statistics, 2022)
One of the important problems faced in Indonesia is poverty. Poverty in question is a condition where people cannot meet the basic needs of life. Based on data from the Central Statistics Agency (BPS), access to basic services is divided into three categories, namely access to drinking water services, access to basic sanitation services, and access to health facilities. The method that will be used on the data on the proportion of households with access to basic services in Indonesia in 2020-2021 is a hierarchical cluster analysis which aims to group provinces in Indonesia into clusters according to their similarities, and to see the effect of COVID-19 on the population. household access using Wilcoxon Signed-Rank. The results of the hierarchical cluster analysis using the average linkage method, the proportion of households with access to basic services in 2020 and 2021 is divided into 7 clusters where the cluster with the highest proportion is occupied by DI Yogyakarta Province and the cluster with the lowest proportion is occupied by Papua Province, and there are differences in average Average of the proportion of household access to basic services during the COVID-19 pandemic and after the COVID-19 pandemic.